Explosive atmospheres. Non-electrical equipment for explosive atmospheres. Non-electrical type of protection constructional safety ''c'', control of ignition sources ''b'', liquid immersion ''k'' Part 37, (30th June 2016) - British Standards Institution,
No abstract available